(untitled) (Research, Society and Development, 2025)
Promoting child health through awareness of the vaccination schedule for indigenous children is extremely important today, as it positively influences the reduction of preventable diseases. This study aims to report on an action developed in the Kainã Village, in the municipality of Manaquiri-AM, which used participatory methodologies to engage indigenous children in a dialogue about the importance of vaccines, the vaccination schedule, booster shots, and maintaining their vaccination records. The methodology included prior research and practical activities with puppet theater, games, and educational dynamics, providing a playful and welcoming environment. The action was carried out with children from the Kainã Village, located in the municipality of Manaquiri-AM, to inform them about the importance of vaccines in preventing diseases. The children actively participated and showed interest, facilitating their understanding of the content. It is concluded that educational actions with a culturally sensitive and participatory approach are effective in promoting indigenous child health and strengthening the bond between the community and health professionals.